Study of population trends - Thompson, Warren Simpson, 1887-1950.; Whelpton, Pascal K. (Pascal Kidder), 1893-
Study of population trends submitted for publication by Thompson and Pascal K. Whelpton.
Demographer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States -- Population -- Statistics; Demographers